If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -6) = 2x + 4 Reorder the terms: 2(-6 + 3x) = 2x + 4 (-6 * 2 + 3x * 2) = 2x + 4 (-12 + 6x) = 2x + 4 Reorder the terms: -12 + 6x = 4 + 2x Solving -12 + 6x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + 6x + -2x = 4 + 2x + -2x Combine like terms: 6x + -2x = 4x -12 + 4x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + 4x = 4 + 0 -12 + 4x = 4 Add '12' to each side of the equation. -12 + 12 + 4x = 4 + 12 Combine like terms: -12 + 12 = 0 0 + 4x = 4 + 12 4x = 4 + 12 Combine like terms: 4 + 12 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| (x*x)+6x-5=0 | | -20x^2-14x-7=0 | | 6(2+3)+1+3-(-5)= | | 9-2c+6c=29 | | a+5=1/5(15+5a) | | 10x-(2)=-32 | | 2x-4+x+7=90 | | -9(x-5)+9=3x+42 | | 51-(3+6x-2(x+3))=5(4x-3)-(5(x-1)-16c+6) | | 6x=-16 | | -12+-3x=-12 | | 9+n=1+6n | | -4(1+3n)+7n=3(n-2)-6 | | -6-x+3=-4 | | 50000=20x-.001x^2 | | q-11=-5 | | 6/12-3/4 | | 2(7r-6)+6(6+5r)=24 | | 2(x+1)=-13-3x | | 6y+2(y-2)=8y-2(y-10) | | 8-8x=86-36x | | 3(1+6n)=-19+7n | | 13(x+6)=11 | | 18-4x=2(1+6x) | | 10-3x=15x+2x | | 5/3x+1/3x=71/3+8/3x | | -5+7x=5+5x | | 5/3x+1/3x=71/3 | | 9+n=-1+6n | | 2x^2-8bx=-6b^2 | | 24=-8n | | M-(5-2m)-(4m+11)=5m-13 |